2006
DOI: 10.1002/jcb.21012
|View full text |Cite
|
Sign up to set email alerts
|

Limited plasticity of mesenchymal stem cells cocultured with adult cardiomyocytes

Abstract: In order to assess, in a controlled in vitro model, the differentiation potential of adult bone marrow derived stem cells we have developed a coculture procedure using adult rat cardiomyocytes and mesenchymal stem cells (MSCs) from transgenic GFP positive rats. We investigated in the cocultured MSCs the time course of cellular processes that are difficult to monitor in in vivo experiments. Adult rat cardiomyocytes and adult rat MSCs were cocultured for up to 7 days and analyzed by confocal microscopy. Several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 35 publications
5
40
1
Order By: Relevance
“…This induction toward the cardiomyocyte lineage is presumably induced by local cell-to-cell contact and/or the presence of soluble factors in the coculture medium. For example, previous studies have shown that MSCs can establish connections with cardiomyocytes through gap junction channels composed of connexin-43 [21,39,[47][48][49][50], a gene that we found was induced in our GFP ϩ MSCs. MSCs with gap junction connections to cardiomyocytes do not generate APs (in agreement with our findings) but can affect electrical conduction by electrotonic interactions, thereby either inducing [48] or preventing [47,49,50] arrhythmias.…”
Section: Discussionmentioning
confidence: 63%
“…This induction toward the cardiomyocyte lineage is presumably induced by local cell-to-cell contact and/or the presence of soluble factors in the coculture medium. For example, previous studies have shown that MSCs can establish connections with cardiomyocytes through gap junction channels composed of connexin-43 [21,39,[47][48][49][50], a gene that we found was induced in our GFP ϩ MSCs. MSCs with gap junction connections to cardiomyocytes do not generate APs (in agreement with our findings) but can affect electrical conduction by electrotonic interactions, thereby either inducing [48] or preventing [47,49,50] arrhythmias.…”
Section: Discussionmentioning
confidence: 63%
“…Rat bone marrow stromal cells were harvested and cultured as described by Gallo et al 19 Briefly, bone marrow cells were isolated from the bone marrow of femurs by flushing the medium into the bone shaft. The cell suspension was filtered through a 40 µm nylon filter (Falcon) and plated at a density 2.5×10 3 /cm 2 in chambers of 24-well plates.…”
Section: Cell Culturesmentioning
confidence: 99%
“…28 It is unknown for how long the elevated cytokine concentrations are needed in the healing heart and for how long they remain beneficial. Too widespread and prolonged overexpression of growth and angiogenesis factors may increase the risk for hemangioma growth, and the observed fate of MSCs after 8 to 9 days may be advantageous.…”
Section: S252 Circulation September 15 2009mentioning
confidence: 99%